Guerra internacional, revolución y dictadura: los partidos parlamentarios y la política peruana entre 1865 y 1867 - Peralta Ruiz, Víctor (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
This article studies the political behavior of the first Peruvian parliamentary parties between the constitutional government of General Juan Antonio Pezet and the Dictatorship of General Mariano Ignacio Prado. I argue that the revolutionary option in 1865 and 1867 was conditioned by the way the government conducted its diplomatic conflict with Spain, in the first case, and by how the dictatorship made use of the political gains of the naval conflict of May 2 1866, in the second. That is to say, unlike other countries involved in the Spanish diplomatic question, international war conditioned the Peruvian political system. In particular, international war becomes an explanatory factor for the main parliamentary parties’ coup intentions, having felt circumstantially excluded by the executive office.

Este artículo estudia el comportamiento político de los primeros partidos parlamentarios del Perú entre el gobierno constitucional del general Juan Antonio Pezet y la dictadura del general Mariano Ignacio Prado. Se argumenta que la opción por la revolución en 1865 y 1867 estuvo condicionada por la forma en que el gobierno condujo el conflicto diplomático con España, en el primer caso, y en cómo la dictadura procesó los réditos políticos de la jornada naval del 2 de mayo de 1866, en el segundo caso. Es decir, a diferencia de otros países implicados en la cuestión española, la guerra internacional condicionó el sistema político peruano y es un factor explicativo de la actuación golpista de sus principales partidos parlamentarios al sentirse estos coyunturalmente excluidos por el poder ejecutivo.
International War, Revolution, and Dictatorship: Parliamentary Parties and Peruvian Politics between 1865-1867
Keywords: Revolución; Siglo Xix; Perú; Juan Antonio Pezet; Mariano Ignacio Prado; https://purl.org/pe-repo/ocde/ford#6.01.01